How it affects me: the effects of arguments in public debates on marriage equality for young people in Taiwan - Lee, I-Ching (Frontiers in Psychology, 2025)
How do arguments in public debates regarding same-sex marriage affect young people? The literature has suggested three possible effects. These debates may affect young people, regardless of their sexual identities, due to the fact that young people widely share a set of values pertaining to human rights and equality (H1). These debates may affect sexual minority individuals more strongly than heterosexual individuals because the arguments used in such debates are targeted at sexual minority individuals (H2). Alternatively, these debates may affect positive and negative outcomes in different ways depending on the nature of the arguments (H3). Two experimental studies (N = 92 and N = 411) were conducted in Taiwan with the goal of testing these three hypotheses. The evidence revealed by these studies largely supported the first hypothesis. The effects observed were similar across young people with different sexual identities and various types of outcomes: reading arguments in support of same-sex marriage increased positive emotions (in both studies) and reduced negative emotions (in Study 2) in comparison with a control condition. Further implications regarding young people's responses to social changes are discussed.